Impaired fear learning and extinction, but not generalization, in anxious and non-anxious depression. (March 2021) - Wurst, Catherina; Schiele, Miriam A.; Stonawski, Saskia; Weiß, Carolin; Nitschke, Felix; Hommers, Leif; Domschke, Katharina; Herrmann, Martin J.; Pauli, Paul; Deckert, Jürgen; Menke, Andreas
Abstract: Fear conditioning and generalization are well-known mechanisms in the pathogenesis of anxiety disorders. Extinction of conditioned fear responses is crucial for the psychotherapeutic treatment of these diseases. Anxious depression as a subtype of major depression shares characteristics with anxiety disorders. We therefore aimed to compare fear learning mechanisms in patients with anxious versus non-anxious depression. Fear learning mechanisms in patients with major depression (n = 79; for subgroup analyses n = 41 patients with anxious depression and n = 38 patients with non-anxious depression) were compared to 48 healthy participants. We used a well-established differential fear conditioning paradigm investigating acquisition, generalization, and extinction. Ratings of valence, arousal and probability of expected threat were assessed as well as skin conductance response as an objective psychophysiological measure. Patients with major depression showed impaired acquisition of conditioned fear. In addition, depressed patients showed impaired extinction of conditioned fear responses after successful fear conditioning. Generalization was not affected. However, there was no difference between patients with anxious and non-anxious depression. Results differed between objective and subjective measures. Our findings show altered fear acquisition and extinction in major depression as compared to healthy controls, but they do not favor differential fear learning and extinction mechanisms in the pathogenesis of anxious versus non-anxious depression. The results of impaired extinction warrant future studies addressing extinction learning elements in the treatment of depression.